Developing and matching skills in the online platform economy: Findings on new forms of digital work and learning from Cedefop’s CrowdLearn study - Davies, H; Lehdonvirta, V; Margaryan, A; Albert, J; Larke, LR (Cedfop, 2020)
Long before the outbreak of the Covid-19 crisis, questions were raised about gig and platform work: are they ‘digital sweatshops’ or a conduit to skills development and better skills matching? The public health crisis may have accentuated the vulnerability of platform workers, but it also demonstrated the wider potential for working and learning digitally.